Counseling Interventions for Domestic Violence Cases Among Young Adult Couples: A Case of Kira Police Division Station - Patience Mirembe (Uganda Christian University, 2023)
The study sought to investigate the counseling interventions for domestic violence cases among young adult couples using a case of Kira police division station. It was guided by three objectives namely; to find out the factors that contribute to the increase of domestic violence cases among young adult couples, to determine the most prevalent type of counseling intervention among young adult couples and to assess the effectiveness of counseling interventions in reducing cases of domestic violence among young adult couples. The study used a cross sectional research design using both quantitative and qualitative approaches. Simple random and Purposive sampling techniques were used to select a sample of 24 respondents. Data was collected using questionnaires and interview guide. The results show that several factors contribute to domestic violence cases among young adult couples which were financial constraints, untreated mental health issues, lack of effective communication, unrealistic expectations and resistance to change. The counselor centered and client centered counseling interventions were widely used as prevalent type of counseling intervention among young adult couples. The effectiveness of counseling interventions in reducing cases of domestic violence among young adult couples included temporary relief, Couples are in position to make informed decisions, reduction in future consequences, promotion of harmony among the couples and making couples appreciate each other. The study recommends that there is need for the young adult couples to continue seeking for the counseling services as they can address some of the challenges they are faced with, the need for the police to increase on resources for family Unit of the police and massive sensitization in the communities about the dangers of domestic violence and look for the ways to address them.
This is a dissertation.